2023
DOI: 10.1051/epjconf/202327911003
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the 86Kr(α,n)89Sr cross section at energies relevant for the weak r-process

Abstract: The r-process has been shown to be robust in reproducing the abundance distributions of heavy elements, such as europium, seen in ultra-metal poor stars. In contrast, observations of elements 26 < Z < 47 display overabundances relative to r-process model predictions. A proposed additional source of early nucleosynthesis is the weak r-process in neutrino-driven winds of core-collapse supernovae. It has been shown that in this site (α,n) reactions are both crucial to nucleosynthesis and the main source of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…The results in this work are also important for applications of the “solid–gas” nanocomposite films as Ne (and Ar) solid targets for nuclear reaction experiments of interest in astrophysics and nuclear structure studies [ 28 , 29 , 32 , 33 ]. These solid targets can overcome the limitations of cryogenic or gas cell-based systems, which are bulky and difficult to handle, thus facilitating usage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results in this work are also important for applications of the “solid–gas” nanocomposite films as Ne (and Ar) solid targets for nuclear reaction experiments of interest in astrophysics and nuclear structure studies [ 28 , 29 , 32 , 33 ]. These solid targets can overcome the limitations of cryogenic or gas cell-based systems, which are bulky and difficult to handle, thus facilitating usage.…”
Section: Discussionmentioning
confidence: 99%
“…An exhaustive microstructural characterization also showed that gas content and nanobubble size and shape are finely tunable [ 17 , 24 , 25 ]. Due to the high density and pressure of He trapped in the nanobubbles [ 24 , 25 , 26 , 27 ], the He-charged Si films have been proposed as “solid targets” for nuclear reaction studies in our previous works [ 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Psaltis et al (2022) went a step further and explored the impact of nuclear physics uncertainties on predictions of elemental abundance ratios and compared them with observations of Galactic metal-poor stars. Both studies have motivated several experimental studies in the nuclear astrophysics community (Kiss et al 2021;Szegedi et al 2021;Angus et al 2023, for example).…”
Section: Weak R-processmentioning
confidence: 99%
“…An exhaustive microstructural characterization also showed that gas content and nanobubbles size and shape are finely tunable [17,24,25]. Due to the high density and pressure of He trapped in the nanobubbles [24][25][26][27], the He-charged Si films have been proposed as "solid-targets" for nuclear reaction studies in our previous works [28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%